Use of Educational Technologies and the Possibility of Integrating the Flipped Classroom in the Teaching of the French Language in Moroccan Schools - Er-Razine, Tareq; Barbara, Rahma; Idrissi Aydi, Ouafae (Pedagogika, 2023)
This study explored the integration of ICTE in the Moroccan education system, focusing on the potential adoption of flipped classrooms for teaching French. 106 teachers participated, showcasing strong technological skills. However, most of them were not familiar with the pedagogy of flipped classrooms. Nevertheless, they expressed eagerness for training, indicating the potential for successful adoption and bridging the gap between technology and effective teaching in Moroccan schools.